Ebogotermes raphaeli, new genus and new species, an African soldierless termite described from the worker caste (Isoptera, Termitidae, Apicotermitinae) - Scheffrahn, Rudolf H.; Roisin, Yves; Akama, Pierre Dieudonné; Šobotník, Jan (Zootaxa, 2021)
Ebogotermes raphaeli gen. n. sp. n., is described from workers collected in Cameroon. This soil-feeding termite is the largest soldierless termite from central Africa and aligns with the Anoplotermes subgroup. The enteric valve armature is weakly armed and, as with most apicotermitine species, is uniquely diagnostic.